2018
DOI: 10.1021/acs.iecr.8b02217
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anticorrosion Performance and Mass Preparation of Magnetic Metal-Doped Zinc Oxide Nano Solid Solutions

Abstract: To enhance the limited anticorrosion property of ZnO nanoparticles (NPs), magnetic metal-doped ZnO nano solid solutions (M-ZnO NSSs, M = Fe, Co, Ni) were synthesized by a calcination modification method. Through investigating the electron transfer postponement by magnetic metals and sediment layer obstructing erosion by electrolytes, a synergistic anticorrosion mechanism was concluded. In comparison with ZnO NPs, the impedance of Fe-, Co-, and Ni-doped ZnO NSSs dramatically increased by 757.0%, 1067.4%, and 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The decrease of both Tafel anode and cathode slopes of Cu-HAP (Table ) indicates that the spin polarization of Cu-HAP effectively promotes the electron transfer. In addition, the weak magnetism of the sample induces a deflection of the path of motion of the anodically generated electrons . The electron transfer to the cathode slows down or decreases, leading to the inhibition of the whole corrosion electrochemical process.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of both Tafel anode and cathode slopes of Cu-HAP (Table ) indicates that the spin polarization of Cu-HAP effectively promotes the electron transfer. In addition, the weak magnetism of the sample induces a deflection of the path of motion of the anodically generated electrons . The electron transfer to the cathode slows down or decreases, leading to the inhibition of the whole corrosion electrochemical process.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous research of our group, it was also confirmed that ZnO-based DMS could be used as an effective corrosion inhibitor to enhance the protection of coatings on ferrous substrates. 14 In studying magnetic metal-doped ZnO nanosolid solutions, Xue 15 et al found that the Lorentz force generated by the micromagnetic field can control the anode electrons to achieve the effect of inhibiting corrosion. What is more, the application of ZnO-based binary/multiple nanomaterials in photocatalysis is also very compelling.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most researchers have tried to solve these problems by compounding the ZnO material with other materials or by designing combined structures. , Although these methods can provide excellent corrosion inhibitors, they cannot optimize the properties of the ZnO material. However, elemental doping makes it possible. …”
Section: Introductionmentioning
confidence: 99%